Implementación de una máquina trituradora de botellas de plástico en la empresa ecom en la ciudad de Santo Domingo de los Tsáchilas para minimizar la contaminación ambiental - Changoluisa Toaquiza, Angela Vanessa (2022)
Nowadays there is polymer PET recycling, this recycled material can be used to generate several products or even make new containers, this idea was generated based on the need to transform this material into reusable. The purpose of this work is to implement a plastic bottle crushing machine in the company ECOM in Santo Domingo de Los Tsáchilas to minimize environmental pollution. To fulfill this purpose, the following guidelines are developed: Identify the needs of the ECOM company, determine the basic characteristics of the bottle crushing machine, evaluate design alternatives and desirable parameters, size and design the different components of the crushing machine, and implement this machine to the processes of the company and commissioning. Within the work, an exhaustive investigation was carried out to determine the existing problems, as well as the observation of the company needs to have a bottle crusher with certain specific characteristics. With the implementation of the machine in the crushing processes, the labor force can be optimized by reducing it to 70%, in a standard way, since the number of operators involved in the process is reduced.